BRAIN MACHINE INTERFACE: ANALYSIS OF SEGMENTED EEG SIGNAL CLASSIFICATION USING SHORT-TIME PCA AND RECURRENT NEURAL NETWORKS - C.R., Hema; M.P., Paulraj; R., Nagarajan; Yaacob, Sazali; Adom, Abdul Hamid (Iraqi Journal for Electrical and Electronic Engineering, 2008)
Brain machine interface provides a communication channel between the human brain and an external device. Brain interfaces are studied to provide rehabilitation to patients with neurodegenerative diseases; such patients loose all communication pathways except for their sensory and cognitive functions. One of the possible rehabilitation methods for these patients is to provide a brain machine interface (BMI) for communication; the BMI uses the electrical activity of the brain detected by scalp EEG electrodes. Classification of EEG signals extracted during mental tasks is a technique for designing a BMI. In this paper a BMI design using five mental tasks from two subjects were studied, a combination of two tasks is studied per subject. An Elman recurrent neural network is proposed for classification of EEG signals. Two feature extraction algorithms using overlapped and non overlapped signal segments are analyzed. Principal component analysis is used for extracting features from the EEG signal segments. Classification performance of overlapping EEG signal segments is observed to be better in terms of average classification with a range of 78.5% to 100%, while the non overlapping EEG signal segments show better classification in terms of maximum classifications.